GRAPHIC ORGANIZERS IN THE DEVELOPMENT OF THE PRODUCTION OF EXPOSITIVE TEXTS IN STUDENTS OF THE IV PRIMARY EDUCATION CYCLE OF THE I.E. 65058 IN THE DISTRICT OF MANANTAY -2018 - Dávila Talepcio, Judith (2019)
The objective was to demonstrate that the application of the graphic organizers develops the production of expository texts in the fourth cycle students (third and fourth grade) of primary education of the I.E 65058 - 2018; the type of study was explanatory, the quasi-experimental design with pre and post test and control group, the sample consisted of 240 students, 124 students were the experimental group and 120 students were the control group, a test was used as an instrument text production that was applied as a pre and post test that was subjected to a process of validation and reliability, the results were: in the production texts in the pretest both the control group (51.67%) and experimental group ( 52.42%) were found in the Start level, while in the post test the experimental group (46.77) was found in achievement level and the control group (53.33%) was in process.The general conclusion was that the application of the graphic organizers in the post test significantly improved the production of expository texts in the students of the experimental group reaching the level of achievement, confirmed by the hypothesis test t> 0.05; Likewise, in the planning and textualization dimensions, the application of graphic organizers was significant t> 0.05. KEYWORDS: graphic organizers, text production, planning.